Americas: Selected Verse and Vignette - Lee, A. Robert (Biblioteca Javier Coy d'estudis Nord-Americans, 2017)
Americas: Selected Verse and Vignette? seeks to give expres¬sion in poem and metaphor to the United States as a perso¬nally lived and engaged-with culture. The span, accordingly, involves both site and journey, a roster of art, people, different authorships, film, music, photography, cities, society. Prose sketches both serious and antic as well as verse. American Studies with a difference. 'Americas: Selected Verse and Vignette? busca dar expresión mediante la poesía y la metáfora a los Estados Unidos como un ser vivo comprometido con la cultura. El alcance, en consecuencia, implica tanto un lugar como un viaje, una alineación de arte, personas, diferentes autorías, cine, música, fotografía, ciudades, sociedad. Fragmentos serios y absurdos, tanto en prosa como en verso. Unos estudios americanos diferentes.